An investigation of digital scholarship and disciplinary culture in Oman - Al-Aufi, Ali; Genoni, Paul (Library hi tech, 2010)
Purpose - The purpose of this paper is to investigate disciplinary differences in the use of networked information for research and scholarly communication at Sultan Qaboos University (SQU), Oman. The paper produced quantitative data on how and why academics within different disciplines utilise networked information either made available internally through the university library, or externally through services accessed by the internet.Design methodology approach - A questionnaire survey was conducted with academic staff at SQU.Findings - Statistical analysis found a number of significant differences between respondents in the science disciplines and those in the social sciences and humanities with regard to their use of, and attitudes towards, digital information services. While respondents from science disciplines show overall longer and more frequent use of networked information, respondents from humanities and social sciences indicated more positive attitudes towards library networked services.Research limitations implications - The Arab country context presents a challenge in determining the degree to which results can be extrapolated to other environments, in that disciplines are also divided by language. Science disciplines teach in English, and the social science and humanities in Arabic.Originality value - While similar studies have been undertaken in developed countries, this study is an attempt to establish some data for a developing Arab country.